Prevalence of Anal Squamous Intraepithelial Lesions in HIV-1–Infected Young Men Who Have Sex With Men and Transwomen. Issue 4 (October 2018) - Thompson, Amelia B.; Gillespie, Scott E.; Mosunjac, Marina B.; Hussen, Sophia A.; Flowers, Lisa C.; Camacho-Gonzalez, Andres F.
Abstract : Objective: Anal cancer rates are increasing among HIV-infected persons. Although an efficacious human papillomavirus (HPV) vaccine is available, HPV vaccination rates remain low. Therefore, providers perform anal cancer screening, but there is no consensus on the optimal methods or timing of screening. This study was performed to determine the prevalence of and factors associated with anal squamous intraepithelial lesions in sexually active HIV-infected young men who have sex with men and transgender women. Materials and Methods: We performed a single-center, retrospective study of sexually active HIV-infected young men who have sex with men and transgender women aged 13 to 24 years at an HIV clinic in Atlanta GA from 2009 to 2016. We used analysis of variance and χ 2 tests of independence to evaluate bivariate associations and identify demographic, behavioral, and clinical risk factors. Results: Of 314 subjects with a mean (SD) age of 20.4 (2.1) years at initial anal cytology testing, 5% had completed the HPV vaccine series at or before the time that cytology was obtained. Ninety-five percent of the anal cytology tests obtained were abnormal, and 72 (29%) of those subjects returned for diagnostic testing either by intraoperative biopsy or high-resolution anoscopy. Fifty-seven percent of those who underwent biopsy had histologic high-grade squamous intraepithelial lesions including 2 cases of carcinoma in situ. A history of greater than 20 lifetime sexual partners was associated with abnormal histology (probability < 0.001, p = .017). Conclusions: Our study highlights the value of early, standardized screening to avoid missing anal dysplasia or cancer, particularly in unvaccinated persons with high numbers of sexual partners.